Entre estudos, leituras, maternidade e trabalho: análise semiótica de histórias de vida de estudantes da área de Letras da UFT - Reis, Naiane Vieira dos (2021)
This thesis aims to analyze the school and academic paths based on the narratives of students enrolled in a public university in the northern region of the country who are also mothers and workers. More specifically, we intend to understand the intersection between studies, work and motherhood, owing to the sexual division of labor that leads, but not precisely determines, women to the field of social reproduction, domestic space and unpaid service. Based on the considerations of gender studies, concentrated in several areas of research, especially in history, sociology, philosophy, in dialogue with linguistics, in the field of discourse, we turn to look at the memories about the performances of students in the context of professional training, in view of the care work, the time divided between multiple tasks and the more or less asymmetric relationships experienced in their fields of activity. Adopting a qualitative research approach, this work takes Oral History as methodological support for data generation, selecting 18 semi structured interviews with working student-mothers as a cut-off for discussion and analysis, in which memories about schooling in basic and higher education, were recorded, combined with motherhood and work. Discursive Semiotics, a theory of discourse that is interested in the way in which meaning is constructed, subsidizes the woven analyzes, being also considered the contributions of Tensive Semiotics in the discussion about memory, and of sociosemiotics in the problem of sensitive interaction. Upon entering the scope of professional training, whether at undergraduate or graduate level, students combine, in a more or less conflictual way, the demands of motherhood and work outside the university, being paid and/or unpaid. The larger and more consistent the support community for academics, at work, at university and at home, in the field of social reproduction, the less the educational background of the participants is configured as a barrier to be overcome by women. Qualification in the field of work, in addition to being stated as a desirable object-value, an academic want-to-be, with a view to socially valued training, is also shaped as a must-be that favors conditions of social insertion in better paid careers for the working class. In the relationship with educational institutions, the most appropriate interactions with the social actors who operate there favor the permanence of the student-mother in these spaces, as well as the continuity of studies, verified mainly in the stories of the participants who had children during basic education or undergraduation and continued at more advanced levels of academic life. In addition, heterogeneous forms of resistance are observed from the participants, considering the roles of genders with whom they negotiate, reproduce and, at the same time, reject, whether at home, at university or at work. In this sense, professional training is being addressed as a challenge and achievement, because it makes it possible for women to build a career in the paid labor market, a less socially vulnerable social reproduction space, as well as trajectories in academic life.